Gender preferences of work outcomes over the course of time: a cross- sectional study in Israel. Issue 5 (3rd September 2019) - Sharabi, Moshe; Simonovich, Javier; Shahor, Tal
ABSTRACT: This cross-sectional study examines changes in the importance of the valued work outcomes among Israeli men and women aged 25 years and over. Overall, gender differences have been declining over the years. Moreover, among both women and men there was decrease in the importance of the intrinsic outcome of interest and the social outcome of serving society at the expense of the dramatic increase in the importance of the extrinsic outcome of income. These trends reflect a continuing transformation from a more collectivist and altruistic society to a more individualistic and materialistic society.